COMMUNITY-DRIVEN DEVELOPMENT INFRASTRUCTURE AND PRODUCTIVE ASSETS’ SUSTAINABILITY FOR LIVELIHOOD IN RURAL COMMUNITIES IN OGUN STATE, NIGERIA - Adeniyi, Adekunle A (Journal of Continuing and Development Education, 2023)
This study focused on community-driven development infrastructure and productive assets’ sustainability for livelihood in rural Fadama communities in Ogun state, Nigeria. Two research questions and e two hypotheses guided the study. Descriptive survey design of the ex-post facto type was adopted, using multi-statge sampling technique to select two hundred participants from rural Fadama communities in the twenty local government areas of Ogun state, Nigeria. Data for the study were collected with a modified Community-driven Infrastructure and Productive Assets’ Sustainability for Livelihood Scale, subjected to reliability test using Cronbach Alpha test of internal consistency, which yielded 0.86. Data were analysed using descriptive statistics including frequency counts, percentages and inferential statistics i.e multiple correlation matrix at 0.05 level of significance. Correlation analysis showed that there is a positive significant relationship between community-driven development variables and sustainability; ownership/control (.417), participation (r=.393), capacity-building (r=.292), decision-making (r=.382); and positive significant relationship between livelihood and community-driven development infrastructure (r=.393) and community-driven development productive assets (r=.618). Therefore, the two null hypotheses are rejected. It is concluded that the adoption of community-driven development variables in rural development will guarantee positive project impacts, project sustainability and positive influence on livelihood of beneficiaries. It is recommended that rural development stakeholders should direct more funds towards community-driven development projects.